Immune checkpoint-based biomarkers for therapeutic response in patients with multiple sclerosis - López-Molina, MariPaz; Torres Iglesias, Gabriel; Sáenz de Santa María-Diez, Gonzalo; Valentín-Quiroga, Jaime; Laso-García, Fernando; Gallego, Rebeca; Pozo-Novoa, Javier; Chamorro, Beatriz; López-Collazo, Eduardo; Puertas, Inmaculada; Díez-Tejedor, Exuperio; Gutiérrez-Fernández, María; et al. (Frontiers in Immunology, 2025)
IntroductionAlthough numerous disease-modifying treatments have been introduced for multiple sclerosis (MS), approximately 25% of patients experience therapeutic failure. This underscores the urgent need for reliable, minimally invasive biomarkers to predict treatment response at early stages. This study aimed to investigate 22 circulating immune cell subpopulations and their immune checkpoint (IC) expression profiles to identify early immunological biomarkers indicative of therapeutic failure in MS patients.MethodsIn this observational and prospective study, 119 patients with relapsing-remitting MS were enrolled, including 69 responders and 50 non-responders, and 29 healthy controls. Spectral flow cytometry was used to immunophenotype 22 immune cell subpopulations and quantify the expression of co-stimulatory and co-inhibitory ICs before and at three months post-treatment initiation. Their correlation with therapeutic response over 12 months in MS patients was also analyzed. The response to treatment was evaluated using the No Evidence of Disease Activity composite, which includes clinical relapses, new lesions on MRI and progression of motor disability.ResultsWe identified differential IC expression patterns between MS patients and healthy controls, revealing specific ICs involved in the disease. Within the MS cohort, we observed differences between treatment responders and non-responders. Responders exhibited higher CD70 expression on Natural Killerbright cells. Additionally, elevated inhibitory CTLA-4 levels on CD20-CD27+ B cells may serve as biomarker for disability progression. BTLA expression on CD20+CD27- B cells was associated with relapse events, and PD-L1 expression on Natural Killerbright cells appeared to be a potential biomarker for progression independent of relapse activity (PIRA).DiscussionThese findings highlight that specific immune cell subpopulations and their IC expression profiles can serve as valuable, early, and minimally invasive immunological markers for predicting therapeutic response in MS patients.